The Process of Increasing the Protective Effectiveness of HARDOX Steel by Way of Selective Thermal and Thermo-Chemical Processing - Andrzej ZIŃCZUK (Problemy Mechatroniki)
The work presents the influence of selective thermal and thermo-chemical processing on the protective properties of an example ballistic plate made of HARDOX 500 steel. A novel process that does not require advanced thermal processing appliances and has led to changes in the crystallographic structures in various layers of the material is presented. The presented laboratory and field testing results show that it is possible to achieve a class of ballistic resistance similar to that of thicker plates made of the same steel.